Correlation between Low Grade Inflammation with Endothelial Progenitor Cells Surface Marker in Hypertension - Widjaja, Johnson; Bakri, Syakib; Donosepoetro, Marsetio (Universitas Padjadjaran, 2012)
Patients with hypertension have been shown to express reduced number and functional capacity of endothelial progenitor cells (EPCs). Recent study reveals that EPCs contain an important capability to maintain endothelial integrity and vascular homeostasis. Therefore, enhancement of EPCs could be benefit for individuals with cardiovascular diseases. We investigated the correlation between low grade inflammation marker (hsCRP) with EPC surface marker (CD34 total) in hypertension. This was an observational study with cross sectional design conducted in 51 nonhypertenive and 60 hypertensive subjects. hsCRP (as marker of inflammation) was measured by immunochemiluminometric method. CD34 total (as marker of EPC) was measured by flow cytometry method. hsCRP concentration was higher in hypertensive subjects compare to nonhypertensive subjects (mean±SD, 2.709±2.50 vs 2.476±2.438 mg/L; P>0.05). CD34 total level was lower in hypertensive subjects compare to nonhypertensive subjects (mean±SD, 1.957±0.858 vs 3.244±3.463/μL; P<0.05). hsCRP had positive correlation with CD34 total in hypertensive subjects (P<0.05). The increasing concentration of hsCRP will stimulate the CD34 total level in hypertensive subjects as demonstrated by the positive correlation between hsCRP with CD34 total.Key words: hsCRP, CD34 total, endothelial progenitor cell, hypertensionKorelasi antara Inflamasi Tingkat Rendah dengan Endothelial Progenitor Cells Surface (EPCs) Marker pada HipertensiAbstrakPasien dengan hipertensi menunjukkan penurunan jumlah dan fungsi kapasitas Endothelial Progenitor Cells (EPCs). Penelitian terkini mengungkapkan bahwa EPCs memiliki kemampuan penting untuk memelihara integritas endotelial dan homeostasis pembuluh darah. Oleh karena itu, peningkatan kapasitas EPCs bermanfaat bagi individu dengan penyakit kardiovaskular. Penelitian ini menginvestigasi korelasi antara marker inflamasi tingkat rendah (hsCRP) dengan marker EPC surface (total CD34) pada hipertensi. Penelitian ini merupakan studi observasional dengan desain cross sectional pada 51 orang nonhipertensi dan 60 orang pasien hipertensi. hsCRP (marker inflamasi) diukur menggunakan metode immunochemiluminometric. Nilai total CD34 (marker EPC) diukur dengan menggunakan metode flow cytometry. Konsentrasi hsCRP lebih tinggi pada pasien hipertensi dibandingkan pada pasien nonhipertensi (mean±SD, 2,709±2,0 vs 2,476±2,438 mg/L; P>0,05). Nilai total CD34 lebih rendah pada pasien hipertensi dibandingkan dengan pasien nonhipertensi (mean±SD, 1,957±0,858 vs 3,244±3,463/μL; P<0,05). hsCRP memiliki korelasi positif dengan total CD34 pada pasien hipertensi (P<0,05). Peningkatan konsentrasi hsCRP akan menstimulasi level total CD34 pada pasien hipertensi seperti yang ditunjukkan dengan korelasi positif antara hsCRP dengan total CD34.Kata kunci: hsCRP, total CD34, endothelial progenitor cell, hipertensi